IDETIFIKASI INDEKS KINERJA REVETMENT PENGAMAN PANTAI PULAU RUPAT - Guspi; Manyuk Fauzi; Imam Suprayogi (Racic : Rab Construction Research, 2026)
The coastal area of Rupat Island has a high level of vulnerability to abrasion and sea waves, requiring coastal protection structures in the form of revetments to protect the shoreline area. Along with the increasing age of the structures, the physical condition and function of the revetments have deteriorated due to the continuous influence of waves and sea currents. This study aims to identify the performance index of coastal revetment structures on Rupat Island based on the Guidelines for Operation and Maintenance of Coastal Protection Structures SE No. 01/SE/M/2011. The research was conducted through inventory surveys, monitoring, and evaluation of the physical condition of the structures in several villages on Rupat Island. The performance index assessment was carried out based on the condition of structural components, including the crest, outer slope, outer foundation, outer mattress, and armor layer, using weighting values according to the revetment structure type. The results showed that the condition of the revetments on Rupat Island varied from good, fairly good, requiring repair, to heavily damaged categories. The highest index value was found in RV Segment 1A with a value of 3.80, categorized as heavily damaged, while most other segments were classified as fairly good with index values ranging from 1.90 to 2.50. Several segments, such as RV Segments 2E–2J, 6K–6L, 10Q–10AD, and 11C–11J, were categorized as requiring repair due to structural deterioration. The most dominant damage occurred in the armor and outer mattress components due to continuous wave and sea current action. Based on the evaluation results, routine maintenance, rehabilitation, and priority handling are required for segments with high damage levels to maintain the optimal function of coastal protection structures.